Teamwork in Schools under the Office of Chanthaburi Primary Educational Service Area 1 - เลาหพันธุ์, เมทิกา; แก้วมงคล, ทรงยศ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This research aimed to: (1) examine teamwork in educational institutions; (2) compare teamwork in schools classified by position, work experience, and school size; and (3) explore guidelines for enhancing teamwork in educational institutions. The sample consisted of school administrators and teachers under the Office of Chanthaburi Primary Educational Service Area 1. The sample size was determined using Yamane’s formula (1967) for calculating. A stratified sampling technique (simple stratified sampling) was employed, yielding a total of 317 participants. School size was used as the sampling unit, and simple random sampling by lottery method was applied to select the participants. The research instrument was a five-point Likert scale questionnaire. The Index of Item-Objective Congruence (IOC) ranged from 0.60 to 1.00. The reliability coefficient of the instrument was .980. Data were analyzed using a statistical software package. The statistics employed included frequency, percentage, mean, and standard deviation. Inferential statistics consisted of t-test and F-test (One-way ANOVA). Content analysis           The research findings revealed that: 1) The overall level of opinions regarding teamwork in educational institutions was at a high level. 2)When comparing administrators and teachers, there was no statistically significant difference in their overall opinions toward teamwork in schools. However, when considering each aspect individually, a statistically significant difference at the .05 level was found in the aspect of participation. In contrast, when classified by school size and years of experience in the current position, there were no statistically significant differences in overall opinions or in any individual aspects of teamwork. 3)The guidelines for developing teamwork in educational institutions consisted of six key components: 1) communication, 2) shared goals, 3) mutual trust, 4) participation, 5) coordination, and 6) collaboration.